Efficacy of neoadjuvant pertuzumab in addition to chemotherapy and trastuzumab in routine clinical treatment of patients with primary breast cancer: a multicentric analysis - Fasching, Peter Andreas; Hartkopf, Andreas D.; Gass, Paul; Häberle, Lothar; Akpolat-Basci, Leyla; Hein, Alexander; Volz, Bernhard; Taran, Florin-Andrei; Nabieva, Naiba; Pott, Birgit; Overkamp, Friedrich; Einarson, Hanna; et al. (Breast cancer research and treatment, 2019)
PurposeNeoadjuvant combination treatment with chemotherapy (CTX), trastuzumab (TZM), and pertuzumab (PTZ) has been shown to result in higher pathological complete response rates (pCR) in comparison with treatment with chemotherapy and trastuzumab (CTX/TZM). This analysis was aimed at real-world validation of these results from prospective randomized trials.MethodsIn a retrospective analysis conducted in the PRAEGNANT network, patients were eligible for inclusion if they had either received neoadjuvant therapy with CTX/TZM or chemotherapy, trastuzumab, and pertuzumab (CTX/TZM/PTZ) and subsequently underwent surgery for their primary breast cancer. The effect of the two neoadjuvant regimens on pCR in addition to commonly applicable predictors of pCR was analyzed in 300 patients from three study sites, using logistic regression analyses with treatment arm, age, clinical tumor stage, grading, and hormone receptor status as predictors.ResultspCR with complete disappearance of all tumor cells was seen in 30.2% (n = 58) of patients treated with CTX/TZM and in 52.8% (n = 57) of those treated with CTX/TZM/PTZ. CTX/TZM/PTZ was positively associated with pCR (adjusted odds ratio 2.44; 95% CI 1.49-4.02). Mastectomy rates were not influenced by the therapy.ConclusionsThe results of clinical trials were confirmed in this dataset of patients who were treated outside of clinical trials in everyday routine work. pCR rates can be improved by 20% with pertuzumab in routine clinical use.
First online: 15 October 2018
Gesehen am 25.06.2019